Diversity of parasitic plants and their hosts in Kepala Jeri and Pemping agroforestry Batam Indonesia - Solikin Solikin (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2017)
Parasitic plants lived by adhering, absorbing water, minerals and food to host plants. The objective of this research was to determine the diversity of the parasitic plants and their hosts in agroforestry lands where farmers cultivated various plants around their houses or forests. The research was conducted in Kepala Jeri and Pemping Islands, Batam, Riau Islands Province in October 2014 using exploration methods. Plant inventory and data collection were done along determined exploration tracks. There were three species of the parasitic plants were found namely Cassytha filiformis L., Dendrophthoe pauciflora Dans. and Viscum stenocarpum Dans. The most dominant parasitic plant was C. filiformis, whereas the least dominant parasitic plant was V. stenocarpum. There were 26 species, from 24 genera and 17 families of host plants of C. filiformis whereas hosts of D. pauciflora were 15 species, from 12 genera and 9 families.